Pengembangan E-Modul Berbasis Android Menggunakan Sigil Software Pada Pembelajaran Fiqih Kitab Fathul Qorib di Pesantren - Abdul farid; Fatima Al-Hammadi (https://ejournal.insuriponorogo.ac.id/, 2026)
Fiqh learning in Islamic boarding schools is generally still dominated by lecture methods and the use of yellow books without harakat, especially on the material of buying and selling, usury, and khiyar in the Book of Fathul Qorib. This condition causes students to experience difficulties in understanding the material independently and has an impact on low independence and learning comprehension. Therefore, this study aims to develop an Android-based Fiqh learning e-module using Sigil Software and test its level of validity, practicality, and effectiveness. This research is a development research (Research and Development) using the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of eighth grade students of Miftahul Istiqomah Islamic Boarding School. Data collection techniques used expert validation questionnaires, practicality questionnaires, and pretest and posttest tests. Data were analyzed descriptively quantitatively. The results of the study showed that the developed e-module has a very valid level of validity based on the assessment of material experts (92.5%), media experts (86.54%), and language experts (92.5%). The practicality of the e-module is categorized as very practical based on practitioner assessments (95%) and student responses in small group trials (96.67%). The effectiveness of the e-module shows an increase in student learning outcomes with an N-Gain value of 0.808, which is in the high category. Thus, the developed Android-based Fiqh learning e-module is declared valid, practical, and effective as a supporting teaching material for Fiqh learning in Islamic boarding schools.